Formation of Cun+ (n=1−3), Arn+ (n = 1, 2), and ArCu+ ions during sputtering of a copper surface by low-energy Ar+ ion bombardment in a dilute argon atmosphere. (29th June 2018) - Hippler, Rainer; Denker, Christian
Abstract: Formation of monoatomic Ar + and Cu +, diatomic Ar 2 +, ArCu +, and Cu 2 +, and triatomic Cu 3 + ions during 500 eV Ar + ion bombardment of a copper surface in a dilute argon atmosphere was investigated by means of energy-resolved mass spectrometry. Energy spectra of Ar n + ( n  = 1, 2), Cu n + ( n = 1 − 3 ), and ArCu + ions show distinct features which are related to the specific formation processes taking place in the plasma region and during ion bombardment of the Cu cathode.